Comparative Study on the Effects of Silicon Nanoparticles and Cellulose Nanocrystals on Drought Tolerance in Tall Fescue (Festuca arundinacea Schreb.) - Meng Li; Sile Hu; Xulong Bai; Jie Ren; Kanliang Tian; Huili Zhang; Zhilong Zhang; Vanquy Nguyen (Plants)
Tall fescue (Festuca arundinacea Schreb.) is a herbaceous species that is commonly used for ecological slope restoration in China. However, water scarcity often constrains its growth due to the unique site conditions of steep slopes and climate-induced drought stress. This study aims to compare the ameliorative effects of silicon nanoparticles (Si NPs) and cellulose nanocrystals (CNCs) on drought stress in tall fescue and to elucidate their underlying mechanisms of action. The results indicated that drought stress impaired photosynthesis, restricted nutrient absorption, and increased oxidative stress, ultimately reducing biomass. However, Si NPs and CNCs enhanced drought tolerance and promoted biomass accumulation by improving photosynthesis, osmotic regulation, and antioxidant defense mechanisms. Specifically, Si NP treatment increased biomass by 48.71% compared to drought-stressed control plants, while CNCs resulted in a 33.41% increase. Transcriptome sequencing further revealed that both nanomaterials enhanced drought tolerance by upregulating genes associated with photosynthesis and antioxidant defense. Additionally, Si NPs improved drought tolerance by stimulating root growth, enhancing nutrient uptake, and improving leaf structure. In contrast, CNCs play a distinct role by regulating the expression of genes related to cell wall synthesis and metabolism. These findings highlight the crucial roles of these two nanomaterials in plant stress protection and offer a sustainable strategy for the maintenance and management of slope vegetation.